2020
DOI: 10.3389/fneur.2019.01391
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Cytokines and Chemokines as Predictors of Stroke Outcomes in Acute Ischemic Stroke

Abstract: Conclusions: Machine learning algorithms can be employed to develop prognostic predictive biomarkers for stroke outcomes in ischemic stroke patients, particularly in regard to identifying acute gene expression changes that occur during stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 69 publications
1
31
0
Order By: Relevance
“…To date, a number of studies have demonstrated that the blood levels of cytokines, chemokines, and growth factors, including C-reactive protein, TNF-α, IL-6 and IL-10, are associated with outcomes in AIS patients [14][15][16]. Although IL-2 is one of the most frequently studied cytokines in stroke patients, the conclusions are ambiguous and inconsistent with the results of experimental studies [17][18][19]. This might be due to the complexity of IL-2/IL-2R autocrine loops.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a number of studies have demonstrated that the blood levels of cytokines, chemokines, and growth factors, including C-reactive protein, TNF-α, IL-6 and IL-10, are associated with outcomes in AIS patients [14][15][16]. Although IL-2 is one of the most frequently studied cytokines in stroke patients, the conclusions are ambiguous and inconsistent with the results of experimental studies [17][18][19]. This might be due to the complexity of IL-2/IL-2R autocrine loops.…”
Section: Discussionmentioning
confidence: 99%
“…A dysregulated immune response, accompanied by an increased number of inflammatory cells, high TNF-α production and the activation of microglia cells has been shown to enhance neuroinflammation and exacerbate ischemic brain injury in patients with IS and a mouse model of cerebral ischemia ( 11 ). Inflammatory cytokines and chemokines have been used as predictors of stroke incidence and outcomes ( 12 , 13 ). Thus, the genetic variation of inflammatory cytokine genes has become a critical issue in research relating to the predictive risk factors of IS occurrence ( 14 , 15 ), as well as its severity and outcome ( 16 ), and this provides potential therapeutic options for the treatment of inflammatory diseases ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we reported that genes related to a Th2 autoimmune response are elevated in intracranial blood from subjects during thrombectomy. 8 Changes in CCL23 support the gene data as CCL23 is induced by interleukin 4, a classic Th2 cytokine. 22 Proteins are drug targets for ischemic stroke.…”
Section: Discussionmentioning
confidence: 58%